Pengaruh Kompensasi Terhadap Kinerja Karyawan pada PT. Sunlife Financial Unit Syariah Cabang Kota Medan - Suci Ardi, Amalia Ramadhani; Syahriza, Rahmi (Universitas Labuhanbatu, 2021)
Companies that have good performance come from employees who also do a good job. However, there are factors that encourage the employee to do a good job, namely by providing compensation. By providing compensation, the employee will be more enthusiastic in doing work. Employees at PT. Sunlife Financial Unit Syariah Medan City Branch did their job well but the compensationoi was not commensurate with the work they had done. Therefore, thexpurpose of thisi studye was too determineyYwhether compensation hasi anw effecto oni employee performancem at PT. Sunlife Financial Unit Syariah Medan City Branch or due to other factors. Thes methodt usedi inm thismHstudy isq a quantitativeq methodl withp aw samplel ofl 30 which was carried out randomly (random sampling). Data collection techniques using questionnaires or questionnaires distributed to employees at PT. Sunlife Financial Unit Syariah Medan City Branch. BThe datam analysisp techniqueq usedo iso multipleo linearq regressionianalysis whichlnwas previouslyo tested with normalityr testw, multicollinearityw testp, bheteroscedasticity testq, autocorrelation testb, tw testa and coefficientj ofl determinationqltest. yThe resultsw ofy thisl studyw are thato compensation has a significantp positive effectpMon employee performance at PT. Sunlife Financial Unit Syariah Medan City Branch where thekuvalue ofo tp counto (2,191) > tm tableo (2,045).